Virtuosity and the Musical Work: The Transcendental Studies of Liszt - Samson, Jim (Cambridge Cambridge University Press, 2007)
This book is about three sets of etudes by Liszt: the Etude en douze exercices (1826), its reworking as Douzes grandes études (1837), and their reworking as Douzes études d'exécution transcendante (1851). At the same time it is a book about nineteenth-century instrumental music in general, in that the three works invite the exploration of features characteristic of the early Romantic era in music. These include: a composer-performer culture, the concept of virtuosity, the significance of recomposition, music and the poetic, and the consolidation of a musical work-concept. A central concern is to illuminate the relationship between the work-concept and a performance- and genre-orientated musical culture. At the same time the book reflects on how we might make judgements of the 'Transcendentals', of the Symphonic Poem Mazeppa (based on the fourth etude), and of Liszt's music in general.
Keywords: Liszt, Franz -- 1811-1886; 19th Century (1801-1900); Étude; Piano; Composing; Virtuosity; Performance